Comparison of outcomes after transcatheter aortic valve implantation following home versus non-home discharge. Issue 4 (9th June 2022) - Hebeler, Katherine R.; Ogola, Gerald; Filardo, Giovanni; Mack, Michael; Stoler, Robert; Mixon, Timothy; Szerlip, Molly; Edgerton, James; Hebeler, Robert F.
Abstract: As more patients undergo transcatheter aortic valve implantation (TAVI), knowledge of 1-year mortality and associated factors becomes increasingly important. After other cardiac procedures, discharge location has been shown to be associated with 1-year mortality. We examined outcomes of TAVI patients discharged home vs an extended care facility (ECF). All TAVI patients from January 1, 2012, to December 31, 2017, were evaluated. Cox proportional hazard regression models with cubic splines were used to estimate the adjusted effect of discharge to ECF on 1-year mortality. A total of 957 (85.6%) patients discharged home were compared to 160 (14.3%) discharged to ECF. On univariate analysis, patients discharged home were younger and had a lower Society of Thoracic Surgeons Predicted Risk of Mortality, higher albumin, and fewer vascular complications and strokes. Patients discharged to ECF had a higher 30-day mortality (3.8% vs. 0.5%, P = 0.001) and 1-year mortality (25.7% vs. 8.3%, P < 0.001). Cox proportional hazard regression models showed increased risk of 1-year mortality for patients discharged to ECF. In conclusion, patients discharged to ECF had a higher 30-day and 1-year mortality. The strongest predictor of 1-year mortality was discharge to ECF. Society of Thoracic Surgeons Predicted Risk of Mortality score was not a predictor of 1-year mortality.